Astroglial Connexins as a Therapeutic Target for Alzheimer's Disease - Yi, Chenju; Koulakoff, Annette; Giaume, Christian (Current Pharmaceutical Design, 2017)
Background: In Alzheimer's disease (AD), modification of astrocytic properties is a well-known and documented fact, but their involvement in pathophysiology has only been examined in recent years. One distinct hallmark of AD is reactive gliosis which are represented in microglial and astrocytic phenotype changes. This reactive gliosis has been associated with changes in the expression and function of connexins. Connexins are proteins that can form gap junction channels and hemichannels, and in a disease context, have shown increased expression in astrocytes that contact amyloid plaques in vivo. Amyloid plaques are aggregates of the amyloid-beta protein, which present in the AD brain in patients and in animal models. Methods: Murine AD models demonstrate changes in connexin channel activity which mirror in cell culture systems treated with amyloid-beta peptide. This has been closely studied in the familial AD mouse model APPSwe/ PS1dE9 where the implications of connexin channel functions have been examined. Results: These studies demonstrate that while gap junctional communication was unaffected, hemichannel activation could be detected in the astrocytes of hippocampal slices containing amyloid-beta plaques. Most critically, the activation of hemichannels is associated with the release of gliotransmitters (such as ATP and glutamate) which results in the maintenance of a high intracellular free Ca2+ concentration within astrocytes, which initiates the start of a vicious cycle. Strategies that target astroglial connexin hemichannels include the knocking out of the connexin 43 gene in astrocytes of the APPSwe/PS1dE9 mice, as well as using various pharmacological tools. This results in the decrease of gliotransmitter release and the alleviation of neuronal damage. This includes the reduction of oxidative stress and neuritic dystrophies in neurons that are typically associated with plaque formation in the hippocampus. Concusion: In this review, we summarize recent findings on astroglial connexin channels in the neurodegenerative process of Alzheimer's disease, and discuss how this can be a strategy in AD treatment to block the activity of hemichannels in astrocytes.
Keywords: gap junction